Recomposição da vida religiosa: Estudo das relações entre indivíduo e comunidade em congregações femininas - Garcia, Martina Maria Eudosia Gonzáles (2006)
Women religious congregations experience a re-composition in the context of the contemporary modernity, establishing new sociable links between the individual and the forms of life and common action. This re-composition process is introduced due to the emergence of the individualism exists in the Women Religious Life. Institutional mechanisms lose legitimation power on the members while these enlarge the margin of freedom and autonomy. This context allows to build more equalitarian relationships, opens space for the difference and the plurality where women are more attentive to their subjectivity and needs. The relationships are elaborated from the individual experience and the subjects of the group who interact to each other, so as to broaden the society to form a sense and action. A dialectic accompanies this process in formation and the constant effort makes the building up of communities possible who try to establish a balance between the individual accomplishment and the common commitment through co-operation, dialogue and by overcoming of conflicts. This work discourses by the relationships that establishes between individual and community in areas of power, action and daily religious living